2000
DOI: 10.1002/1099-1611(200011/12)9:6<462::aid-pon485>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Clinical follow-up after bilateral risk reducing (?prophylactic?) mastectomy: mental health and body image outcomes

Abstract: Background: In Manchester, approximately 120 women at ≥1: 4 lifetime risk of breast cancer have considered preventative surgery since 1992. Women treated within the Manchester protocol receive two genetic counselling sessions, a psychological assessment and a surgical consultation pre‐operatively and annual follow‐up post‐operatively. The vast majority of women have breast reconstruction. Methods: Since 1996, mental health and body image have been assessed in women attending annual follow‐up using self‐report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
1
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 35 publications
0
72
1
10
Order By: Relevance
“…This was not the case for the 64 women who declined surgery. In contrast to Hopwood et al (43), the level of sexual discomfort and degree of sexual pleasure did not change significantly over time in either of the two groups.…”
Section: Satisfaction and Regret Following Prophylactic Mastectomycontrasting
confidence: 96%
“…This was not the case for the 64 women who declined surgery. In contrast to Hopwood et al (43), the level of sexual discomfort and degree of sexual pleasure did not change significantly over time in either of the two groups.…”
Section: Satisfaction and Regret Following Prophylactic Mastectomycontrasting
confidence: 96%
“…Early studies found no evidence of a negative sexual impact in 79 women who opted for RRM up to 18 months post-surgery [19] and only minor deteriorations in body image in 76 women who had RRM up to three years prior [20]. In contrast, Brandberg et al [21] reported significant reductions in body image and sexual pleasure in 90 unaffected women one year after RRM, and more recent findings suggest these negative impacts continue at least up to two years following RRM [15,22].…”
Section: Introductionmentioning
confidence: 99%
“…9 Risk-reducing surgery (mastectomy, salpingo-oophorectomy) does not eliminate risk, 10 and is not without possible compromise to quality of life and psychological well-being. 11 Prenatal diagnosis (PND) followed by termination of a pregnancy (TOP) carrier fetus 12 is an alternative for known BRCA mutation carriers who want biological children not carrying the mutation. Concerns have been raised that PND for (breast) cancer predisposition represents a perversion of the original intention to protect people from the fate of an early, painful death or severe disability, and falls within the realm of deciding the 'desirability' of a particular life.…”
Section: Introductionmentioning
confidence: 99%